2007
DOI: 10.1002/cne.21324
|View full text |Cite
|
Sign up to set email alerts
|

Development of starburst cholinergic amacrine cells in the retina of Tupaia belangeri

Abstract: "Starburst" cholinergic amacrines specify the response of direction-selective ganglion cells to image motion. Here, development of cholinergic amacrines was studied in the tree shrew Tupaia belangeri (Scandentia) by immunohistochemistry with antibodies against choline acetyltransferase (ChAT) and neurofilament proteins. Starburst amacrines expressed ChAT much earlier than previously thought. From embryonic day 34 (E34) onward, orthotopic and displaced subpopulations segregated from a single cluster of immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 100 publications
(144 reference statements)
4
13
0
Order By: Relevance
“…Next we have investigated the development of cholinergic amacrine cells in the retina of Tupaia belangeri (Knabe et al, 2007). Through the optimization of standard immunohistochemistry protocols, cholinergic amacrine cells which play key roles "in originating retinal directional selectivity and optokinetic eye movement" (Yoshida et al, 2001) could be detected 2 weeks earlier than had been reported previously (Sandmann et al, 1997).…”
Section: "Starburst" Amacrine Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…Next we have investigated the development of cholinergic amacrine cells in the retina of Tupaia belangeri (Knabe et al, 2007). Through the optimization of standard immunohistochemistry protocols, cholinergic amacrine cells which play key roles "in originating retinal directional selectivity and optokinetic eye movement" (Yoshida et al, 2001) could be detected 2 weeks earlier than had been reported previously (Sandmann et al, 1997).…”
Section: "Starburst" Amacrine Cellsmentioning
confidence: 99%
“…Different from photoreceptor cells in mice and men, the nuclei of these cones are not stacked upon one another, but clearly arranged in only one row. Consequently, both the development of cones and rods (Knabe, 1995;Knabe and Kuhn, 1996a, b, 1997, 1998a and the establishment of the associated neural networks can be studied under particularly favorable conditions (Müller and Peichl, 1991a, b;Engelmann and Peichl, 1996;Sandmann et al, 1997;Knabe et al, 2007). On the other hand, the tree shrew retina is consulted in clinical contexts due to its extensive structural similarity to the primate retina, e.g., for documentation of retinal thinnings following induced high myopia via in vivo optical coherence tomography (Abbott et al, 2009(Abbott et al, , 2011.…”
Section: "Lens Mitochondria" In the Cone Inner Segmentsmentioning
confidence: 99%
See 3 more Smart Citations